Detection of promoter methylation of tumor suppressor genes in serum DNA of breast cancer cases and benign breast disease controls - Sturgeon, Susan R.; Balasubramanian, Raji; Schairer, Catherine; Muss, Hyman B.; Ziegler, Regina G.; Arcaro, Kathleen F. (Epigenetics, 2012)
Tumors are capable of shedding DNA into the blood stream. This shed DNA may be recovered from serum or plasma. The objective of this study was to evaluate whether pyrosequencing promoter DNA in a panel of 12 breast cancer-related genes (APC, BRCA1, CCND2, CDH1, ESR1, GSTP1, HIN1, P16, RARβ, RASSF1, SFRP1 and TWIST) to measure the degree of methylation would lead to a useful serum-based marker of breast cancer. Serum was obtained from women who were about to undergo a breast biopsy or mastectomy at three hospitals from 1977 to 1987 in Grand Rapids, MI USA. We compared the methylation status of 12 genes in serum DNA obtained from three groups of postmenopausal women (mean age at blood collection: 63.0 y; SD 9.9; range 35-91): breast cancer cases with lymph node-positive disease (n = 241); breast cancer cases with lymph node-negative disease (n = 63); and benign breast disease control subjects (n = 234). Overall, median levels of promoter methylation were low, typically below 5%, for all genes in all study groups. For all genes, median levels of methylation were higher (by 3.3 to 47.6%) in lymph node-positive breast cancer cases than in the controls. Comparing mean methylation level between lymph-node positive cases and controls, the most statistically significant findings, after adjustment of the false-positive rate (q-value), were for TWIST (p = 0.04), SFRP1 (p = 0.16), ESR1 (p = 0.17), P16 (p = 0.19) and APC (p = 0.19). For two of these four genes (TWIST, P16), the median methylation level was also highest in lymph-node positive cases, intermediate in lymph node-negative cases and lowest in the controls. The percent of study subjects with mean methylation scores ≥ 5% was higher among lymph node-positive cases than controls for ten genes, and significantly higher for HIN1 and TWIST (22.0 vs. 12.2%, p = 0.04 and 37.9 vs. 24.5%, p = 0.004, respectively). Despite relatively consistent variation in methylation patterns among groups, these modest differences did not provide sufficient ability to distinguish between cases and controls in a clinical setting.